Acute Effects of Different Conditioning Activities on Amateur Soccer Players - Silva-Neto, Manoel E.; Oliveira, Saulo F. M.; V. Oliveira, José Igor; Gomes, Willemax S.; Lira, Hugo A. A. S.; Fortes, Leonardo S. (International Journal of Sports Medicine, 2023)
Several warm-up activities are used to prepare soccer players for training and games. However, few studies have focused on comparing different activities (strength vs. stretching) in young and amateur athletes, especially for performance improvement in explosive actions. Thus, in order to compare the effect of four conditioning activities on jump and sprint performances, 12 soccer athletes (age: 19±0.8; weight (kg): 72.8±8.0; height (cm): 180±6.7) performed four warm-up activities: strength exercise (cluster system), combined exercise, plyometric exercise, and static stretching (control). The countermovement jump (CMJ) and 30-meter run (30-m Sprint) were performed 10 min after each experimental condition. A ONE-WAY ANOVA test of repeated measures was conducted with a Tukey’s post-hoc test to compare the conditions. The strength conditioning activity protocol (33.68±2.87) showed a significant difference for the CMJ from static stretching (30.96±3.16) (p>0.05). There were significant differences regarding the 30-m Sprint test between strength conditioning (4.72±0.19) and combined activities (4.71±0.21) compared to static stretching (4.84±0.21) (p>0.05). In conclusion, the combined conditioning activity and strength protocols can be chosen in warm-up activities instead of static stretching (control condition) for improved immediate sprint and jump abilities in amateur soccer players.
Keywords: football; young; strength; explosive